Meningkatkan Soft Skills Siswa SMK Taruna Surabaya Untuk Persiapan Dunia Kerja - Perwi, Darmajanti; Sutrisno, Imam; Desi Tri Cahyaningati; Didik Dwi Suharso (CV. Creative Tugu Pena, 2025)
Soft skills are essential in the modern workplace, particularly for graduates of Vocational High Schools (SMK) who are expected to transition directly into industry. This study analyzes strategies to enhance the soft skills of students at SMK Taruna Surabaya in preparation for professional challenges. Utilizing a qualitative research design with a case study approach, data were gathered through observations, interviews, and questionnaires involving students, teachers, and industry practitioners. The findings reveal that structured soft skills development programs—focusing on communication, teamwork, work ethics, and leadership—significantly improve students’ job readiness. Notably, the study integrates project-based learning, formal soft skills training, and industry collaboration to provide a comprehensive developmental framework. Pre- and post-assessments demonstrate substantial improvement in critical soft skill areas, with time management showing the highest gain (37%). The implementation of project-based learning and industrial internships effectively simulates real-world environments, fostering practical skill application. Furthermore, the study identifies curriculum gaps and emphasizes the importance of sustained collaboration between vocational institutions and industry partners to ensure relevant, continuous soft skills development. These insights offer strategic guidance for vocational schools and policymakers in enhancing curriculum design and strengthening industry engagement.